Peran Word of Mouth Promotion Terhadap Keputusan Berkunjung Wisata Ke Desa Rancakalong: Survey Terdadap Wisatawan Domestik yang Berkunjung Wisata Ke Desa Rancakalong - Ghaisani Shabrina Badzlin; Gilang P Putra; Dally Narif (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Word of mouth is a type of promotion that can be carried out by every industry and every background, by doing promotion, it will make visitors interested and make a decision to visist if the informant conveys it attractively to the listeners. Word of mouth has five indicators, which are talkers, topics, tools, talkingpart, and tracking. The study analyzed word of mouth promotion as a variable X with visiting decisions as variable Y. This study aims to describe and detail the role of word of mouth promotion on the decision to visit tourism to Rancakalong Village. The type of research used is quantitative research with a descriptuve approach and this research is included in corralation research. This research uses a survey method with probability sampling method, with a total of 100 respondents who have visited Rancakalong Village. This study found that word of mouth promotion has a role in tourist visiting decisions and the media is efficient in implementing word of mouth promotion on visiting decisions. And tourists also agree that many tourists visit when an event is held in Rancakalong Village.